2014
DOI: 10.1002/jgt.21798
|View full text |Cite
|
Sign up to set email alerts
|

1‐Factor and Cycle Covers of Cubic Graphs

Abstract: Let G be a bridgeless cubic graph. Consider a list of k 1-factors of G. Let E i be the set of edges contained in precisely i members of the k 1-factors. Let µ k (G) be the smallest |E 0 | over all lists of k 1-factors of G.Any list of three 1-factors induces a core of a cubic graph. We use results on the structure of cores to prove sufficient conditions for Bergecovers and for the existence of three 1-factors with empty intersection. Furthermore, if µ 3 (G) = 0, then 2µ 3 (G) is an upper bound for the girth of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 15 publications
2
45
0
Order By: Relevance
“…This paper focuses on the structure of cores and relates µ 2 , µ 3 to each other and to ω. In [14] it is shown that the girth of a snark G is at most 2µ 3 (G). We show that ω(G) ≤ µ 3 (G), then every µ 3 (G)-core of G is a very specific cyclic core.…”
Section: Conjecture 11 ([3]) Every Bridgeless Cubic Graph Has a Cycmentioning
confidence: 99%
“…This paper focuses on the structure of cores and relates µ 2 , µ 3 to each other and to ω. In [14] it is shown that the girth of a snark G is at most 2µ 3 (G). We show that ω(G) ≤ µ 3 (G), then every µ 3 (G)-core of G is a very specific cyclic core.…”
Section: Conjecture 11 ([3]) Every Bridgeless Cubic Graph Has a Cycmentioning
confidence: 99%
“…[14,94,116,122]. Hypohamiltonian snarks have been studied in connection with the famous Cycle Double Cover Conjecture, see [14] for more details, and Sabidussi's Compatibility Conjecture [40].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, every cubic hypohamiltonian graph with chromatic index 4 must be a snark. In 2015, Steffen [122] published a conjecture on hypohamiltonian snarks-see Problem 3 in Chapter 6. In the recent not yet pub- 3 The chromatic index of a graph is the smallest number of colours necessary to colour the edges of the graph such that any two edges sharing an end-point do not have the same colour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that the Cycle Double Cover Conjecture also has interesting connections with the excessive index of snarks. Indeed, it was proved independently by Steffen and Hou et al. that it is enough to prove the Cycle Double Cover Conjecture for snarks with excessive index at least 5.…”
Section: Introductionmentioning
confidence: 99%